2002
DOI: 10.1016/s0378-1127(01)00474-1
|View full text |Cite
|
Sign up to set email alerts
|

Invasive alien trees and water resources in South Africa: case studies of the costs and benefits of management

Abstract: Invasive alien plants are consumptive water-users, and may have reduced river flows in South Africa by about 6.7% according to a broad-scale study. An effective programme to bring the invasions under control would cost about US$ 92 million per year for the next 20 years. This paper reports on studies of four representative catchments (the Sonderend, Keurbooms, Upper Wilge and Sabie-Sand) to assess the impacts and costs of invasions at a scale that is more relevant to managers. Several alien plant species have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
143
1
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(147 citation statements)
references
References 45 publications
0
143
1
3
Order By: Relevance
“…S.T. Blake) in the Florida Everglades (Turner et al 1998), Pinus species, Eucalyptus species, and others in South Africa (Richardson 1998, Le Maitre et al 2002, lodgepole pine in New Zealand (Ledgard 2001), and Scots pine in Nova Scotia and Ontario (Catling and Carbyn 2005). On the other hand, some intercontinental introductions have resulted in "naturalized" populations with less aggressive behaviour, e.g., Norway spruce in the forests of eastern North America (e.g., Stover and Marks 1998, Hunter and Mattice 2002, PDCNR 2011; sycamore (Acer pseudoplatanus L.) in England (Peterken 2001); or lodgepole pine in Scandinavia (Knight et al 2001).…”
Section: Ecological Consequences Of Assisted Migration Invasion Risk mentioning
confidence: 99%
See 1 more Smart Citation
“…S.T. Blake) in the Florida Everglades (Turner et al 1998), Pinus species, Eucalyptus species, and others in South Africa (Richardson 1998, Le Maitre et al 2002, lodgepole pine in New Zealand (Ledgard 2001), and Scots pine in Nova Scotia and Ontario (Catling and Carbyn 2005). On the other hand, some intercontinental introductions have resulted in "naturalized" populations with less aggressive behaviour, e.g., Norway spruce in the forests of eastern North America (e.g., Stover and Marks 1998, Hunter and Mattice 2002, PDCNR 2011; sycamore (Acer pseudoplatanus L.) in England (Peterken 2001); or lodgepole pine in Scandinavia (Knight et al 2001).…”
Section: Ecological Consequences Of Assisted Migration Invasion Risk mentioning
confidence: 99%
“…1, this assessment is a decision-making step for the modes of AM with higher risk, portrayed by a key question: "Do the benefits of translocation outweigh the biological, social, and economic costs and constraints?" In contrast to smaller weed species, trees that become invasive following assisted migration practices are also likely to be more easily identified and controlled through traditional silvicultural methods (Ledgard 2001, Le Maitre et al 2002; among the trees and shrubs that have been introduced to Britain, it has been observed that extensive control programs have been able to eradicate Rhododendron ponticum L., despite its significant threat to ecosystems (Peterken 2001).…”
Section: Mitigation Of Ecological Consequences At Different Scales Ofmentioning
confidence: 99%
“…Considerable research has been conducted assessing the impacts of invasive plant species on local and regional hydrology (Le Matire et al, 2011). Le Maitre et al (2002) studied the impact of invasive alien trees in the Sonderend, Keurbooms, Upper Wilge, and Sabie-Sand catchments in South Africa. At the time of the study (2002), 44, 54, 2, and 23%, respectively, of each catchment had been invaded by non-native trees resulting in 7.2, 22.1, 6.0, and 9.4% reductions in river flow.…”
Section: Introductionmentioning
confidence: 99%
“…The water-pumping effects of fast-growing tree plantations have been clarified in different ecosystems, such as in semiarid areas (Wilske et al 2009;Tan et al 2011) and wetlands (Le Maitre et al 2002;Hernández-Santana et al 2008;Migliavacca et al 2009). For example, poplar plantations have the potential to extract groundwater and to reduce the water table in wetland ecosystems (Migliavacca et al 2009).…”
Section: Introductionmentioning
confidence: 99%